Turbine Fast Valving Setting Method Based on the Hybrid Simulation Approach; Energies; Vol. 16, iss. 4 - Ruban N. Yu. Nikolay Yurievich; Kievets A. V. Anton Vladimirovich; Andreev M. V. Mikhail Vladimirovich; Suvorov A. A. Aleksey Aleksandrovich (2023, 2023)
Title screen